The Effectiveness of Whatsapp-Based Online Learning in Class Students IV SD Negeri Babakandesa - Ejen Jenal Mutaqin; Neni Nadiroti Muslihah; Nizar Alam Hamdani; Sifa Nurfalah (Social, Humanities, and Educational Studies (SHES): Conference Series, 2021)
This research uses a descriptive qualitative approach with teacher and grade IV student research subjects. The data collection techniques used are questionnaires, interviews, and documentation. Based on the results of research conducted the effectiveness of online learning based on whatsapp is seen from 4 aspects with the results of presentase calculations showing that the quality of learning (39%) with weak criteria, learning level (38%) with weak, intensive criteria (48%) with sufficient criteria and time (58%) with sufficient criteria. Overall whatsapp-based online learning conducted in Babakandesa State Elementary School is considered less effective. Seen from the many problems that occur in the online learning process, including the limitations of internet quota, less stable internet network and difficulty in understanding the material provided by teachers through whatsapp application.